Studies on follicular dynamics and endocrine profile in cyclic non-descript goats - SARATH, T; MEHROTRA, S; AGARWAL, S K; VARSHNEY, V P; HOQUE, M; SHANKER, UMA; SINGH, S K (The Indian Journal of Animal Reproduction, 2023)
The present investigation was conducted to study the follicular dynamics and endocrine profiles in seven nondescript cyclic goats. Follicular population, dimension and corpus luteum development was studied through real time Bmode transrectal ultrasonography. Serum endocrine estrogen, progesterone, tri-iodo-thyronine and thyroxine concentrations were estimated by Radioimmuaoassay. It was recorded that the medium sized and total fo))jcular population was sigoiflcaotly higher on day 12 when compared to day 0, 4, 8, 16 and 20 of the cycle. There was no appreciable difference in follicular diameter between different days. However, the diameter of the large follicle was maximum on day of estrus. The diameter of the corpus Iuteum was found to increase from day 8 reaching maximum by day 16 and .was undetected on day 20 of the cycle. Findings revealed that the peak values of serum estrogen. T3 and T4 concentrations observed on day of estrus were significantly higher as compared to day 4, 8, 12, 16 and 20 of the cycle. The progesterone level started to increase from day 4, attaining peak on day 16, thereafter started declining and reached basal values on day 20 of th cycle.